Cryphonectria naterciae: a new species in the Cryphonectria-Endothia complex and diagnostic molecular markers based on microsatellite-primed PCR. - Bragança, Helena; Rigling, Daniel; Diogo, Eugénio; Capelo, Jorge; Phillips, Alan; Tenreiro, Rogério (Fungal biology, 2011)
In a recent study intended to assess the distribution of Cryphonectria parasitica in Portugal, 22 morphologically atypical orange isolates were collected in the Midwestern regions. Eleven isolates were recovered from Castanea sativa, in areas severely affected by chestnut blight and eleven isolates from Quercus suber in areas with cork oak decline. These isolates were compared with known C. parasitica and Cryphonectria radicalis isolates using an integrated approach comprising morphological and molecular methods. Morphologically the atypical isolates were more similar to C. radicalis than to C. parasitica. Phylogenetic analyses based on internal transcribed spacer (ITS) and β-tubulin sequence data grouped the isolates in a well-supported clade separate from C. radicalis. Combining morphological, cultural, and molecular data Cryphonectria naterciae is newly described in the Cryphonectria-Endothia complex. Microsatellite-primed PCR fingerprinting with (GACA)(4) primer discriminated between C. naterciae, C. radicalis, and C. parasitica.
The following values have no corresponding Zotero field: accession-num: 21872182
Keywords: Ascomycota; Ascomycota: classification; Ascomycota: genetics; Ascomycota: isolation & purification; Chestnut tree; Cork oak tree; Cryphonectria parasitica; Cryphonectria radicalis (GACA)4; DNA; DNA Primers; DNA Primers: genetics; Endothiella gyrosa; Fagaceae; Fagaceae: microbiology; Fungal; Fungal Proteins; Fungal Proteins: genetics; Fungal: genetics; Microsatellite Repeats; Molecular Sequence Data; MSP-PCR; Mycological Typing Techniques; Mycological Typing Techniques: methods; phylogeny; Plant Diseases; Plant Diseases: microbiology; Polymerase Chain Reaction; Polymerase Chain Reaction: methods; Quercus; Quercus: microbiology; RFLP-PCR; Tubulin; Tubulin: genetics

Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo (The Journal of Organic Chemistry, 2004)
The nonempirical assignment of the absolute configuration of (+)-diplopyrone, the main phytotoxin of Diplodia mutila, i.e., an endophytic fungus, widespread in Sardinian oak forests, and considered one of the main causes of cork oak decline, has been approached by two different methods:? (a) the exciton analysis of the circular dichroism (CD) spectrum and (b) the ab initio calculation of the optical rotatory power. Both methods indicate that (+)-diplopyrone is 6-[(1S)-1-hydroxyethyl]-2,4a(S),6(R),8a(S)-tetrahydropyrano[3,2-b]pyran-2-one, so the stereostructure of this important biomolecule is safely determined for the first time. A comparison of advantages and limitations of the two methods of analysis is also presented.
From Duplicate 2 (Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo)
Keywords: absolute configuration; Circular dichroism; DeVoe method; diplopyrone (voyant); Mitosporic Fungi; Mitosporic Fungi: pathogenicity; Models; Molecular; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Optical rotation; Plant Diseases; Plant Diseases: microbiology; Pyrones; Pyrones: chemistry; Stereoisomerism

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R; Perotto, S; Girlanda, M; Vidano, G; Luppi, a M (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R.; Perotto, S.; Girlanda, M.; Vidano, G.; Luppi, a M. (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11050558
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology